Evaluation of Pharmacological Activities of Leaves and Bark of Myristica fatua var. magnifica Extracts: Activities of Leaves and Bark of Myristica fatua var. magnifica Extracts - V, Padmaja; Amgoth, Srinivas Nayak; Chinna M, Eswaraiah (Iranian Journal of Pharmaceutical Sciences, 2019)
Myristica fatua var. magnifica (Beddome) Sinclair belongs to the family Myristicaceae. It is a tree used as an important plant to cure various diseases. In the present study, petroleum ether, ethyl acetate and methanolicextracts ofMyristica fatua were evaluated for its toxicity, potential analgesic, depressant and anti-inflammatory (invitro &in vivo) activities. The extracts of different concentrations wereused to evaluate the toxicity in albino rats and revealed that they are nontoxic at the studied concentration. The appropriate dose range for preclinical study was found to be 200 & 400 mg/kg and used for above said activities through oral administration and exhibited dose dependent response.In anti-inflammatory (in vitro) studies, the percentage of stabilization was found to be 79.66, 80.63 and 85.22 at concentration of 200 mg/ml of MF (Myristicafatua) leaves, bark and standard respectively. Hence present investigation has established some pharmacological evidences to support the folklore claim of MFas analgesic, depressant and anti-inflammatory.